Perspectives of emergency department clinicians on the challenges of addressing low back pain in the emergency setting: A qualitative study. (22nd September 2021) - Davidson, Simon RE; Bolsewicz, Katarzyna; Kamper, Steven J; Haskins, Robin; Petkovic, Dragan; Feenan, Nicole; Smith, Damien; O'Flynn, Michael; Pallas, Jeremy; Williams, Christopher M
Abstract: Objective: To identify and explore ED clinician perspectives on: (i) why patients with low back pain (LBP) present to the ED and are admitted into hospital from ED; (ii) barriers and enablers they face when providing care to patients with LBP; and (iii) strategies to improve the care of patients with LBP, and associated care processes, in the ED. Methods: We undertook a qualitative exploratory study with ED clinicians (medical officers, nurses and physiotherapists) at a tertiary‐level public hospital in New South Wales, Australia, using focus groups and individual interviews. We used thematic analysis to synthesise participant responses to answer the predefined research questions. Results: Twenty‐one clinicians participated (two individual interviews, 19 focus groups). Perceptions about better access to the ED and advanced care within ED were thought to drive presentations to the ED for LBP. Barriers and enablers to optimal patient care included patient‐, clinician‐ and service‐level factors. The main strategies to improve care included a department LBP pathway, modernised patient and clinician resources, better follow‐up options post‐discharge and improved communication between ED and primary care. Conclusion: We identified a range of targets to improve LBP management in ED. Clinicians perceived internal and external factors to the ED as influences of ED presentation and hospital admission. Clinicians also reported that patient‐, clinician‐ and service‐level barriers and enablers influenced patient management in ED. Strategies suggested by clinicians included improved follow‐up options, access to resources and an 'LBP pathway' to support decision making. Abstract : We interviewed 21 ED clinicians (Medical Officers, Physiotherapists and Registered Nurses) to better understand the enablers and barriers to caring for patients with low back pain, as well as possible ways to improve care. Clinicians identified a range of enablers and barriers, which could be broadly grouped into patient‐, clinician‐ and service‐level factors. Suggested improvements to care included a department low back pain pathway, modernised patient and clinician resources, better follow‐up options post‐discharge and improved communication between the emergency department and primary care.